How is the Development of Integrated Marketing Communication (IMC) Research on MSMEs in Indonesia from 2017 to 2023: A Bibliometric Analysis Approach - Muttaqien, Zaenul; Sudarmiatin, Sudarmiatin; Munawaroh, Nuril Aulia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study employed secondary data extracted from scholarly articles in both Indonesian and English sourced through Google Scholar. Utilizing the Publish or Perish software, the inquiry centered on the keywords